(untitled) (Diametros, 2010)
René Descartes’ Meditations on First Philosophy is his most celebrated philosophical work. The book remains one of the most significant and influential works in epistemology, metaphysics and philosophy of mind in the history of Western philosophy. In this paper I examine the relationship between the various hyperbolic doubts, the dreaming, imperfect creator, and evil demon hypotheses in Meditation I. The paper shows that the "painting analogy" occupies a central position in the First Meditation not only because it effectively links together the hyperbolic doubts, but also because it lays the groundwork for the claim that although it may be impossible for us to know things outside us as our thoughts represent them to be, we can know at least the feature of our thoughts themselves. By raising the necessary doubt about our sensible experience and the corporeal world, the "painting analogy" makes the case for the primacy of the intellectual world.